2008
DOI: 10.1097/jes.0b013e31817bfd47
|View full text |Cite
|
Sign up to set email alerts
|

Altered Mechanisms of Thermoregulatory Vasoconstriction in Aged Human Skin

Abstract: Human exposure to cold stimulates cutaneous vasoconstriction by activating both sympathetic reflex and locally mediated pathways. Older humans are vulnerable to hypothermia because primary aging impairs thermoregulatory cutaneous vasoconstriction. This article highlights recent findings discussing how age-related decrements in sympathetic neurotransmission contribute directly to thermoregulatory impairment, whereas changes in local cold-induced intracellular signaling suggest a more generalized age-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…In the present study, cold stress was applied for 120 s, and hence the effects of prolonged vasoconstriction (generally visible beyond 15 min. of exposure to cold stress) were not considered [40]. The initial noradrenergic mechanism consists of excitation of afferent cold sensitive neurons due to localized cold stress which in turn increases the release of norepinephrine from noradrenergic active vasoconstrictor nerves which leads to vasoconstriction of the cutaneous blood vessels through post-junctional a (especially a 2 ) and b receptors [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, cold stress was applied for 120 s, and hence the effects of prolonged vasoconstriction (generally visible beyond 15 min. of exposure to cold stress) were not considered [40]. The initial noradrenergic mechanism consists of excitation of afferent cold sensitive neurons due to localized cold stress which in turn increases the release of norepinephrine from noradrenergic active vasoconstrictor nerves which leads to vasoconstriction of the cutaneous blood vessels through post-junctional a (especially a 2 ) and b receptors [38].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the norepinephrine mediated localized cutaneous vasoconstriction is strongly dependent on the temperature and as the skin temperature increases on withdrawal of the cold stress, the effect of vasoconstriction reduces due to decreasing responsiveness of a 2 -adrenergic receptors. Moreover, the RhoA and Rho kinase pathway and the endothelial NO (which is a highly potent vasodilator agent) synthase pathways are mutually inhibitory [40]. It has been reported that RhoA and Rho kinase down-regulate endothelial NO synthase activity, whereas cyclic GMP dependent protein kinase (PKG), which is a downstream product of nitric oxide metabolism inhibits Rho activation and Rho kinase induced phosphorylation of myosin light chain phosphatase (MLCP) [45,46].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we extend these prior findings by demonstrating that the augmented pressor response to skin surface cooling in older adults is not mediated by an increase in cardiac output. Collectively, these data suggest an augmented vasoconstrictor response may occur in vascular beds, other than the skin, during cooling in older compared with young adults (31).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 This increased risk for hypothermia appears to be due to diminished sympathetic nervous system-mediated reflex vasoconstriction, which allows greater heat loss. 114 Additionally, an older individual is more likely to have health concerns such as diabetes, hypothyroidism, hypopituitarism, or hypertension, which increase the likelihood of cold injury. As older individuals continue an active lifestyle and as advances in medical and surgical treatments extend life, more persons with histories of myocardial infarction and stroke are becoming active in outdoor environments.…”
Section: Special Concerns Children (Prepubescents)mentioning
confidence: 99%